Embodied authorship in feminist and queer zines in the Iberian Peninsula - López Casado, Laura (2021)
The concept of authorship has been profusely contended and addressed during the last decades. Roland Barthes declared the author dead in 1967, but since then, new approaches, ideas, and reflections have prolonged the discussion until the present day. This chapter proposes to navigate through authorship studies in order to examine authorship practices in zines. The Do-It-Yourself movement has always moved through non-conventional authorship, but the paradigm of the zine has changed in the last decades. The popularity of self-publishing also has changed how these practices are understood. Specifically, I will focus on feminist and queer zines within the Iberian Peninsula. The selected object delimitates the study, and, furthermore, it provides the epistemology and methodology to the chapter. A feminist and queer theoretical approach will be fundamental to understand the embodied authorship that has surfaced in these zines.